The Effects of Teaching Transformative Learning on University Students' English Learning Autonomy in China - Wang, Jiaquan; Wendy Hiew; Suyansah Swanto (Global Academic Excellence, 2022)
This study aims to study the effects of implementing the Teaching of Transformative Learning (TTL) on non-English major students’ English Learning Autonomy (ELA) specifically in an English reading course at a university in China. The main features of TTL were embodied in the critical reflection and the rational discourse on the basis on equal and friendly classroom atmosphere. The study utilized a questionnaire on learning autonomy as its research method to collect data from 116 students in the experimental class. Twenty-three items in the questionnaire investigated five aspects of the students’ ELA. The means of the post-test and pretest of the experimental class students’ ELA revealed a significant difference in the TTL. It indicated that the TTL had a good effect on improving the university students’ ELA in the present study. The study hopes to provide a beneficial reference for other scholars who are interested in improving students’ learning autonomy in their teaching practice.